Beyond Objectivity: Language, Truth Production, and Dominant Narratives in Journalism. - Feldberg, Eve K. (Tufts Archival Research Center, 2017)
Through a critical discourse analysis of reporting and national-level writing about the organized student responses to institutional racism and violence at Yale and the University of Missouri, and an examination of my experiences working for a student publication, I explore links between language, power, objectivity, and a supposedly-objective truth. I ask, Whose voices are given authority and space? What is left unsaid and silenced? What is presented as a claim, and what is presented as fact? Answering these questions begins a necessary deconstruction of the presumed existence of a single objective truth, revealing the fallacy of objectivity to both producers and consumers of mainstream media. Ultimately, I conclude that the goals of “fairness” and “balance” in pursuit of objective journalism continue to normalize and uphold systems of oppression, namely white supremacy. This project makes space to begin imagining a future in which specific and experiential knowledge is valued; a future in which the communication of knowledge and information can occur outside hegemonic structures of racism and white supremacy.